Regeneration of Ficus glomerata Roxb., using shoot tips and nodal explants - Hassan, AKM Sayeed; Khatun, Rahima (Bangladesh Journal of Botany, 2010)
Shoot tips and nodal explants from in vitro growing seedlings of Ficus glomerata Roxb. (Moraceae). showed best shoot induction (88%) on MS medium supplemented with 0.5 mg/l BAP, where maximum number of shoots were produced per culture. In vitro raised shoots rooted well on half strength of MS medium with 2.0 mg/l IBA + 0.1 mg/l NAA. The survival rate of regenerated plantlets was 82%. Key words: Ficus glomerata Roxb.; Shoot proliferation; Micropropagation; Acclimatization DOI: 10.3329/bjb.v39i1.5525 Bangladesh J. Bot. 39(1): 47-50, 2010 (June)